Modeling of synchronous generator for the simulation of Synchroconverter - Chowdhury, Monaha; Akter, Ummay Maimona; Noor, Abdullah Al (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.